2020
DOI: 10.1101/2020.10.22.350470
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conditional targeting of phosphatidylserine decarboxylase to lipid droplets

Abstract: Phosphatidylethanolamine is an abundant component of most cellular membranes whose physical and chemical properties modulate multiple aspects of organelle membrane dynamics. An evolutionarily ancient mechanism for producing phosphatidylethanolamine is to decarboxylate phosphatidylserine and the enzyme catalyzing this reaction, phosphatidylserine decarboxylase, localizes to the inner membrane of the mitochondrion. We characterize a second form of phosphatidylserine decarboxylase, termed PISD-LD, that is generat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…When considering whether this was true of Psd1 orthologs in other organisms, we noted that our previous work identified a glycosylation site on the N-terminus of native Psd1, indicating the ER-localized form of the enzyme must contain a TMD and be integral to the ER membrane (Friedman et al, 2018). In contrast, human PISD is alternatively spliced to produce two isoforms; the canonical long isoform (isoform 1) localizes to the IMM and a shorter isoform (isoform 2) exhibits dual localization (when tagged and overexpressed) at mitochondria and LDs (Kumar et al, 2021). Importantly, the LD-localized isoform in human cells does not contain a predicted TMD and likely targets to LDs via an amphipathic -helix (Kumar et al, 2021).…”
Section: Lipid Droplet Localization Of Psd Is Conserved Between Budding and Fission Yeastsmentioning
confidence: 82%
See 4 more Smart Citations
“…When considering whether this was true of Psd1 orthologs in other organisms, we noted that our previous work identified a glycosylation site on the N-terminus of native Psd1, indicating the ER-localized form of the enzyme must contain a TMD and be integral to the ER membrane (Friedman et al, 2018). In contrast, human PISD is alternatively spliced to produce two isoforms; the canonical long isoform (isoform 1) localizes to the IMM and a shorter isoform (isoform 2) exhibits dual localization (when tagged and overexpressed) at mitochondria and LDs (Kumar et al, 2021). Importantly, the LD-localized isoform in human cells does not contain a predicted TMD and likely targets to LDs via an amphipathic -helix (Kumar et al, 2021).…”
Section: Lipid Droplet Localization Of Psd Is Conserved Between Budding and Fission Yeastsmentioning
confidence: 82%
“…Tagging with mNG did not interfere with Psd1 mitochondrial function, as assessed by growth on carbon sources that require respiration (Fig. 1 Recently, work in human cells by Burd and colleagues revealed that the single human PSD, PISD, has multiple spliced isoforms that encode for differentially localized proteins (Kumar et al, 2021). When overexpressed and GFP-tagged, a long isoform of PISD exclusively localized to mitochondria, while a shorter isoform localized to both mitochondria and lipid droplets (LDs).…”
Section: Psd1 Sub-localizes On the Er To A Subset Of Lipid Droplets In Budding Yeastmentioning
confidence: 97%
See 3 more Smart Citations